Plant regeneration of ilex paraguariensis (aquifoliaceaé) by in vitro culture of nodal segments - Sansberro, Pedro Alfonso (2020)
Fil: Mroginski, Luis Amado. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.